Willingness to pay for osteoporosis risk assessment in primary dental care - Helena Christell; Joanna Gullberg; Kenneth Nilsson; Sofia Heidari Olofsson; Christina Lindh; Thomas Davidson (Health Economics Review, 2019)
Background: Fragility fracture related to osteoporosis among postmenopausal women is a significant cause of morbidity. The care and aftercare of these fractures are associated with substantial costs to society. A main problem is that many individuals suffer from osteoporosis without knowing it before a fracture happens. Dentists may have an important role in early identification of individuals with osteoporosis by assessment of dental radiographs already included in the dental examination. The aim of this study was therefore to investigate postmenopausal women's preferences for an osteoporosis risk assessment in primary dental care. Results: Most respondents (129 of 144 (90%)) were willing to pay for an osteoporosis risk assessment in primary dental care. The overall mean willingness to pay (WTP) including respondents that denoted none or zero WTP was 44.60 exteuro (CI 95% 38.46-50.74 exteuro) (median 34.75 exteuro). A majority (80.6%) of the respondents that denoted WTP also gave a motivation for their answer. The two most common reasons denoted for being willing to pay for osteoporosis risk assessment were the importance of early diagnosis and preventive care to avoid fractures (41.0%) and the importance of knowledge of a risk of osteoporosis (26.4%). A majority of respondents (67.8%) considered it valuable if dental clinics would offer osteoporosis risk assessment. Conclusions: Postmenopausal women seem to find it valuable to be offered osteoporosis risk assessment in primary dental care and are willing to pay for such a risk assessment. From a societal perspective early diagnosis of osteoporosis by risk assessment in primary dental care could prevent osteoporotic related fractures and benefit women's health and quality of life, as well as have a major impact on the health-care budget in terms of costsavings.
Keywords: I10; 330; Dental clinics; Health economics; Medico economic; Osteoporosis; Patient acceptance of health care; willingness to pay